Inverse association between Helicobacter pylori infection and childhood asthma in a physical examination population: a cross-sectional study in Chongqing, China - Donghai Wang; Yuxia Chen; Yuan Ding; Jinwei Tu (BMC Pediatrics, 2022)
Abstract Background Childhood asthma has substantial effects on children's health. It is important to identify factors in early life that influence childhood asthma. Accumulating evidence indicates that Helicobacter pylori may protect against allergic diseases. This study aimed to evaluate the relationship between H. pylori infection and pediatric asthma in Chongqing, China. Materials and methods This cross-sectional study included healthy children aged 4–18 years who underwent a 13C urea breath test during medical checkups in 2021. All medical information was extracted from electronic medical records and a big data system. Logistic regression was used to evaluate the association between H. pylori infection and pediatric asthma, and multivariate regression models were adjusted for covariates. Results In our study, 2241 participants, including 1240 boys (55.33%) and 1001 girls (44.67%), underwent urea breath testing (average age: 8.67 ± 2.70 years). Among them, 292 (13.03%) were positive for H. pylori and 152 (6.78%) had asthma. The rates of asthma diagnosis in H. pylori-negative and -positive children were 7.23% and 3.77%, respectively (odds ratio = 1.995; 95% confidence interval: 1.003–3.968; P < .05). Furthermore, family history of asthma and the percentage of eosinophils in routine blood examination were associated with childhood asthma; however, the body mass index, platelet count, and serum vitamin D level were not. Conclusions We demonstrated a significant inverse association between H. pylori infection and pediatric asthma in Chongqing, China. Further studies are required to determine the causal association and underlying mechanisms to prevent and control childhood asthma.